Changes in the Spectroelectrochemical Properties of Copper(Ii) Hexacyanoferrate(Iii) During Electrochemical Insertion of Alkaline Ions - Herrera-Diaz, F; Herrera-Diaz, F (Springer Science and Business Media Deutschland GmbH, 2021)
In this work, the influence of the electrochemical insertion of different alkali ions, e.g., lithium, sodium, and potassium, on the electrochromic properties of copper(II) hexacyanoferrate(III) (CuHCF) was addressed. CuHCF was electrochemically synthesized on FTO substrates, and a nucleation and growth analysis was shown that follows a 3D progressive nucleation with diffusion-controlled growth, which was confirmed by SEM analysis. The spectroelectrochemical study demonstrated that spectral changes were centered into three regions: a green band (506 nm) associated with a charge transfer (FeIII → CuII), a violet band (413 nm) associated with d-d orbital transition for Cu+2 ions, and an ultraviolet band (354 nm) associated with a ligand-metal charge transfer (CN-→ FeIII). This electronic transfer, along with the calculated electrochromic efficiency averages, indicates a relationship between the ionic radius of insertion ions and the deformation generated in CuHCF. An increase in the ionic radius decreases the interatomic charge transfer, which produces a low electrochromic efficiency. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.